Children?s voices: minority language and identity in Ireland and Scotland, Phase 1 of the An Bradan Feasa (ABF) programme - Harris, John (Trinity College Dublin, 2006)
Children?s Voices is a major two-year project to be carried out jointly by Trinity College Dublin, Queens University Belfast, the University of Edinburgh and Sabhal Mor Ostaig. It represents the first phase of the larger ABF programme of research, institutional cooperation and capacity building outlined in an earlier document Minority Languages, community and identity in Ireland and Scotland.
Exhibited at 'Unlocking the Treasures', a colloquium and poster exhibition to mark the launch of the Long Room Hub on June 14th 2006
Keywords: Irish language and children; Minority languages, Ireland; Minority languages, Northern Ireland; Minority languages, Scotland